THE INFLUENCE OF AUDIT TENURE AND AUDIT ROTATION TO THE AUDIT QUALITY: THE CASE OF INDONESIA - Akifan Abi Rafdi; Frank Gruben (Diponegoro Journal of Accounting, 2021)
This research objective is to examine the influence of audit tenure and audit rotation on audit quality. Audit quality is measured using a dummy variable with the option of either audited by big-4 audit firm or non-big-4 audit firm. Audit tenure is measured by the number of years an auditor has a partnership with the same client. Audit rotation is measured using a dummy variable with the option of either a company have an audit rotation or not. The population in this research consist of all manufacturing companies that are listed on IDX in the period of 2018-2020. This research is using a purposive sampling method which means that there are several requirements for a sample to be included. The final number of samples are 153. Logistic regression model is used to analyze the data. The result of this research shows that audit tenure has a negative effect towards audit quality, meanwhile audit rotation doesn’t have any significant influence towards audit quality.